Effects of Pollution on the Haematology of Cyprinus carpio Inhabiting two Government Sponsored Fish Ponds in East Khasi Hills District, Meghalaya, India - Pala , Eva Mary; Khongwir, Shanwell; Jyrwa, Lucy Mary; Suchiang, Proforma (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Adult Cyprinus carpio were collected from two government sponsored fish ponds located at Fish Dale and Laitkyrhong, East Khasi Hills District, Meghalaya, India. The effects of pollutants on haematological parameters of Cyprinus carpio were studied. The results showed a decline in RBC and WBC count and haemoglobin content in fishes collected from Laitkyrhong. Micronucleus assaywas carried out following standard protocols and observations were made using Olympus, BX- 53 image analyser, CellSens Standard (software). Analysis showed a number of micronucleus and nuclear abnormalities of the erythrocytes of Cyprinus carpio from Laitkyrhong as compared to fishes from Fish Dale. Scanning Electron Microscopy study revealed swollen erythrocytes called spherocytes, ruptured erythrocytes and crenations at the erythrocyte membranes while the control erythrocytes showed normal features. The Energy Dispersive X-ray Spectroscopic analysis was by INCA-7582 (Oxford) Energy Dispersive X-ray microanalyser equipped with a Si (Li) high resolution detector attached to the scanning electron microscope, JSM-6360 (Jeol). Differences in the EDS spectra of RBCs from control, Laitkyrhong and Fish Dale fishes were observed to be in terms of Silicon (Si), Aluminium (Al) and Titanium (Ti) were absent in the control sample. The presence of silicon in erythrocytes of fishes inhabiting Fish Dale and Laitkyrhong area suggests that silicon may be the main factor for the various deformities in the haematological parameters of Cyprinus carpio. The deformities observed may affect the growth and survival of these fishes. Therefore, there is a constant need to check the flow of polluted waters in the rearing ponds especially during the rainy seasons. The present study suggests that haematological study may serve as a tool in determining the health of the fish and the type of environment in which it lives.